Chapter Representations of Lothar I in the Liber pontificalis Ravennatis - Schoolman, Edward (Reti Medievali E-Book, 2022)
Lothar looms large in the Liber pontificalis of Ravenna, an episcopal gesta composed after 846 by a local cleric of that city named Agnellus. In its prefatory verse, Lothar was tied to the memory of his grandfather Charlemagne, and afterwards was presented as an ally of the city and its church, a relationship sealed by the service of the bishop George (837-846) as godfather to Lothar's daughter Rotruda. Furthermore, upon the death of Louis the Pious, as part of an embassy attempting to resolve the conflicts between Lothar and his brothers, George sought to affirm Ravenna privileges on the eve of the battle of Fontenoy, an event described quite differently from other sources. Completed following these struggles, the Liber pontificalis of Ravenna used this image of Lothar to further claims of the special status of the city, especially in its independence from Rome and longstanding imperial connections, and actively sought to legitimize Lothar's own position through a juxtaposition with Charlemagne. Although preserved in the accounts of the bishops of Ravenna, the singular efforts to elevate and memorialize Lothar differ from other contemporary institutional chronicles, and underscore the tension inherent in the narrative.